Digital-based educational administration governance in supporting the effectiveness of school academic services - Hilman , Cecep; Hastuti, Rita; Muti, Irma; Fiyul, Arfiani Yulianti; Rohmah, Siti (Indonesian Research Journal in Education |IRJE|, 2026)
The increasing use of digital technology has influenced how educational institutions manage administrative processes and deliver academic services. This study aims to analyze digital-based educational administration governance in supporting the effectiveness of school academic services at SMP IT Al Azami Cianjur. This study uses a qualitative case study design to explore the implementation of digital governance in administrative management. Data were collected through in-depth interviews, observation, and documentation and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings show that digital-based governance supports changes in student data management and academic reporting processes by making information management more organized and accessible. In addition, digital administration strengthens transparency and accountability while increasing stakeholder satisfaction. The study suggests that digital-based educational administration governance supports the improvement of academic services at SMP IT Al Azami Cianjur.